Strategi Meningkatkan Minat Membaca melalui Pemilihan Teks Bahasa Arab yang Menarik di PP Darut Tauhid Patemon - Lusyiana Efendy; Ainur Rofiq Sofa (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to describe the strategies used to increase students' interest in reading through the selection of interesting Arabic texts at the Darut Tauhid Patemon Islamic Boarding School. The low interest in reading Arabic texts among students is the background to the importance of selecting reading materials that suit their interests and needs. The method used in this study is a qualitative descriptive approach with observation, interview, and documentation techniques. The results of the study indicate that the selection of texts that are relevant to the daily lives of students, accompanied by the use of interactive learning methods, can significantly increase reading interest. In addition, teacher involvement in selecting and presenting contextual materials is also a major supporting factor.